Teenage Male with Cough and Recurrent Bruit - Sheema Gaffar; Elliot Tucker (Case Reports in Pediatrics)
A general pediatrician is skilled at continuity; through longitudinal evaluation, they serve as front-line providers in the recognition and referral of unusual pathology. The majority of arteriovenous malformations (AVM) are diagnosed with history and physical examination. AVM are inherently progressive by nature; their expansion is what creates the risk of morbidity. With higher-risk vascular lesions, relative risk is important when discussing management with observation versus with invasive intervention. Size, location, and expected course of progression of the lesion help generate a timeline for action. Collaboration of physicians with diverse expertise generates optimal plan of therapy, particularly when faced with an unusual clinical finding. Genetics referral may be beneficial, as the body of literature on AVM is growing, and databases on associated syndromes are evolving. Establishing concrete follow-up is imperative to assess for recurrence of AVM or development of additional symptoms. This can be with the interventionalist or with the generalist.